Developing a Model Using Homer for a Hybrid Hydrogen Fuel Cell System - Fera Annisa; Mustaqimah Mustaqimah (Rona Teknik Pertanian, 2013)
ABSTRACT. Hydrogen is widely considered be the fuel of the near future. Combined wind/PV energy hybrid systems can be used to sources energy to hydrogen production. This paper describes design, simulation and feasibility study of a hybrid energy system for a household in Malaysia. One year recorded wind speed and solar radiation are used for the design of a hybrid energy system. In 2000 was average annual wind speed in Johor Bahru is 3.76 m/s and annual average solar energy resource available is 5.08 kWh/m2/day. National Renewable Energy Laboratory’s HOMER software was used to select an optimum hybrid energy system. In the optimization process, HOMER simulates every system configuration in the search space and displays the feasible ones in a table, sorted by total net present cost (TNPC). The optimization study indicates that sensitivity analysis of the HOMER is shown in the overall winner which shows that the most least cost and optimize hybrid system is combination of 10 kW of PV array, 1 unit of wind turbine, 2 kW of fuel cell, 120 units of batteries and 6 kW converter as well as 1 kW of electrolyzer so as to generate the minimum COE, $2.423 kWh- 1. Although renewable sources (wind and PV) involved in the power generation, 1 kg of hydrogen was produced in this system.Pengembangan Model Dengan Menggunakan Homer Untuk Sistem Sel Berbahan bakar Hidrogen HibridaABSTRAK. Hidrogen secara luas dianggap sebagai bahan bakar masa depan. Gabungan sistem hibrida energi angin/fotovoltaik dapat digunakan untuk sumber energi produksi hidrogen. Makalah ini menjelaskan desain, simulasi dan studi kelayakan dari sistem energi hibrida untuk rumah tangga di Malaysia. Satu tahun kecepatan angin tercatat dan radiasi matahari digunakan untuk desain sistem energi hibrida. Pada tahun 2000 adalah kecepatan angin rata-rata tahunan di Johor Bahru 3.76 m/det dan rata-rata sumber daya energi surya tahunan yang tersedia adalah 5.08 kWjam/m2/ hari. Software HOMER digunakan untuk memilih sistem energi hybrida optimal. Dalam proses optimasi, HOMER mensimulasikan setiap konfigurasi sistem dalam ruang pencarian dan menampilkan yang layak dalam sebuah tabel, diurutkan berdasarkan total net present (TNPC). Studi optimasi menunjukkan bahwa analisis sensitivitas HOMER ditampilkan dalam hasil keseluruhan yang menunjukkan bahwa paling sedikit biaya dan mengoptimalkan sistem hibrida adalah kombinasi dari 10 kW array PV, 1 unit turbin angin, 2 kW bahan bakar, 120 unit baterai dan 6 kW converter serta 1 kW electrolyzer sehingga menghasilkan COE(cost of energy) minimal, $2,423 kWjam-1. Sumber-sumber terbarukan (angin dan PV) yang terlibat dalam pembangkit listrik, 1 kg hydrogen akan diproduksi dalam sistem ini